A Review Paper on Plasticulture (International Journal of Innovative Research in Engineering & Management, 2023)
In the previous decade, plastics have  achieved tremendous advances in horticulture. Because of its  structural integrity, chemical properties, and versatility,  plastic has become a prominent material in our everyday  lives. Drip irrigation, plastic mulches, packaging and storage  for better product quality, and post-harvest management are  just a few of the numerous uses for plastic in high-tech  horticulture. The use of polymers in agriculture, horticulture,  water management, food grain storage, and other industries  is known as plasticulture. Despite the fact that the number of  agricultural plastic manufacturers has decreased by 40% in  the past 10 years, the use of plastic in horticultural crop  production has risen significantly. The use of plasticulture in  the cultivation of horticultural crops like veggies, tiny fruits,  flowers, plantation crops, and ornamentals helps to minimize  the sometimes severe weather changes that occur in various  parts of the nation, particularly temperature, rainfall, and  wind.
Keywords: Horticulture; Plastic; Plasticulture